Comparison Between Different Humanoid Leg Hip Kinematics Trough Dynamic Simulation - Zorjan, Maja; Hugel, Vincent; Blazevic, Pierre (International Journal of Industrial Engineering and Management, 2011)
A lot of existing humanoid robots have classical orthogonal leg joint kinematics where all pitch, roll and yaw joints are respectively along longitudinal, lateral and vertical axes of the robot’s body. This paper investigates the influence of different rotary joint axis inclination at the hip joints on power distribution and torque versus angular speed for double support motions. The movements under study here are knees flexion/extension, swaying hips move and forward/backward pelvis motion. They are simulated using a dynamic simulator. This study can help to design better motor arrangement and therefore better power distribution. Article history: Received (05.06.2011); Revised (26.10.2011); Accepted (20.10.2011)